2020
DOI: 10.1103/physreve.102.033003
|View full text |Cite
|
Sign up to set email alerts
|

Continuum constitutive laws to describe acoustic attenuation in glasses

Abstract: Nowadays metamaterials are at the focus of an intense research as promising for thermal and acoustic engineering. However, the computational cost associated to the large system size required for correctly simulating them imposes the use of finite-elements simulations, developing continuum models, able to grasp the physics at play without entering in the atomistic details. Still, a correct description should be able to reproduce not only the extrinsic scattering sources on waves propagation, as introduced by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 76 publications
(125 reference statements)
0
7
0
Order By: Relevance
“…Note that collective modes involving the full matrix coupled to the nanoparticle are not taken into account by the DM methods due to the fixed condition. It was shown in recent articles that the matrix can also play a role [51], especially from its damping properties [11], together with the impedance break between the particle and the matrix [52]. Collective modes may appear when nanoparticles are embedded in a host matrix.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that collective modes involving the full matrix coupled to the nanoparticle are not taken into account by the DM methods due to the fixed condition. It was shown in recent articles that the matrix can also play a role [51], especially from its damping properties [11], together with the impedance break between the particle and the matrix [52]. Collective modes may appear when nanoparticles are embedded in a host matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Matrix modes are indeed available at those frequencies as can be seen in figure 5 where the SiO 2 VDOS is represented with a dotted line. Previous work showed that, at the interfaces, modes of the different phases combine together [50,51,52]. This effect could be used to deduce which mode can be transmitted or reflected on the inclusion.…”
Section: Vibrational Density Of State Of Enpmentioning
confidence: 99%
“…In Ref. [64], we proposed to use two different simple rheological models for the spherical and deviatoric parts separately, determining the longitudinal and transverse quality factor. Here, we propose a new model for the transverse modes.…”
Section: Modelmentioning
confidence: 99%
“…We can write down the full complex constitutive elastic tensor G * [64], which is reduced to a 6 × 6 symmetric matrix due to isotropy, imposing the conditions vi…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation